2011
DOI: 10.1364/oe.19.00a733
|View full text |Cite
|
Sign up to set email alerts
|

Meta-materials applications in thin- film sensing and sensing liquids properties

Abstract: This paper is devoted to study one of the most important applications of metamaterials based on Split Ring Resonator (SRR) which is thin-film sensing and sensing liquids properties. We provide a broad overview of thin film deposition methods, depositing the substance material in the gap, under the rings or on the rings. The sensor allows to extract various information about the dielectric properties and the loss from the resonant frequency. The analyses process consists of comparing the resonant shift to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…A (square) implementation of Fig. 1a was developed in [29], where thin films could be detected when deposited in the capacitive loop gap region. An example of Fig.…”
Section: Improved Split-ring Resonator For Microfluidicmentioning
confidence: 99%
“…A (square) implementation of Fig. 1a was developed in [29], where thin films could be detected when deposited in the capacitive loop gap region. An example of Fig.…”
Section: Improved Split-ring Resonator For Microfluidicmentioning
confidence: 99%
“…Consequently, the sensitivity of CWR-RR is calculated as 7.2 MHz/μm. The proposed structure can achieve a larger resonance-frequency shift than the case of split-ring resonator 28 .
Figure 7Simulated shift of the resonance frequency of the EIT-like MM by increasing the thickness of overlayer.
…”
Section: Resultsmentioning
confidence: 95%
“…Huang et al, 2011 studied the performance of metamaterial sensors, and the results showed that the sensitivity and resolution of the sensors can be greatly enhanced by metamaterials. This opens new degrees of freedom in sensor design, which promises a sensitivity boost [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Raghuwanshi and Kumar [19] have analyzed the planar slab optical waveguide having complicated refractive index profile with Finite Element Method (FEM).…”
Section: Introductionmentioning
confidence: 99%